Are over-paid Chief Executive Officers better innovators? - Jouber, Habib (2013)
This paper focuses on the pay level of the highest paid executive directors which we label as “Executive Director’s Organizational Level” (henceforth EDOL) to raise the question if highest paid CEOs invest heavily in innovative projects. Two-stage least squares (2SLS) regressions show that over-paid CEOs are more likely to invest in R y D projects. They highlight moreover both from a “statutory” and an “activist” perspective that CEOs’ intends to invest in value-enhancing innovations are contingent upon compensation committee independence and investor protection level. Check tests reveal that the pay-performance “innovation” effect for option-based compensation is higher than that for stock-based compensation. Within the options (stocks) rewards unvested options (restricted stocks) are the most effective. However we find that over-paid CEOs of low-growth firms achieve less innovation compared to those of high-growth firms. Throughout we reveal that the effect of CEOs performance-pay on innovation is mainly relevant among overconfident managers than non-overconfident ones.